Monitoring of liver and kidney profiles in anesthesiologists working in a regional reference teaching hospital in Northern Italy: analysis of health surveillance data using a linear mixed model - Alborz Rahmani; Guglielmo Dini; Alfredo Montecucco; Luca Priano; Marco Leonetti; Alessia Manca; Bruno Kusznir Vitturi; Paolo Durando (International Journal of Occupational Medicine and Environmental Health)
Objectives Anesthesiologists represent an occupational group exposed to specific occupational hazards, including potential exposure to waste anesthetic gas released during medical procedures. In recent decades, halogenated anesthetic gases, such as desflurane and sevoflurane, have largely replaced nitrous oxide, due to better safety profiles and lower adverse health effects. However, possible long-term effects of low concentration exposures are unknown. A longitudinal analysis of health surveillance data was performed to test for possible changes over time in key markers of liver and kidney function. Moreover, we assessed the appropriateness of applying linear mixed models to occupational health data.